A study on the communication apprehension experienced by selected Filipino college students - Maala, Jan Rainier (Animo Repository, 2018)
For some students, verbal communication in the classroom can produce physical and emotional anxiety that can profoundly affect their ability to succeed in the academic platform. Communication apprehension (CA) is a pervasive, multifaceted phenomenon that has been studied at multiple levels by several researchers. With the use of PRCA-24 (the Personal report of communication apprehension) developed by McCroskey (1985), the researcher aimed to identify predominant type of speaking anxiety experienced by the students in a speech class and how it affects their grades. Using Pearson-r correlation and multiple regression to identify the relationship between the variables, results show that public speaking is the most anxiety-provoking classroom activity for the respondents and that it is significantly correlated with their speech class grades.